Strategies techniques, and approaches to thinking" - Martinez de Castillo, Sandra Luz (Saunders, 1999)
Contra Costa College, San Pablo, CA. Workbook to assist student nurses in critical thinking. Divided into four sections: basic concepts, prioritizing and decision making, clinical situations, and case studies. Three-hole punched with perforated pages.